EFEKTIVITAS BLACK GARLIC UNTUK MENURUNKAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Annaas Budi Setyawan; Siti Khoiroh Muflihatin (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Black Garlic is a fermented product of garlic that can be used as a herbal medicine for hypertension management. Based on the results of phytochemical analysis in black garlic There are several chemical content such as allicin, S-allyl Cystein, flavonoids, and hydrogen sulfide. The content of SAC, allicin, flavonoids and hidrogen sulfide in black garlic is a compound that can be used to lower blood pressure. Objective: The objective of this research is to prove the effect of Black Garlic on reducing blood pressure in hypertensive patients. Methods: The research method used a one group pretest and posttest design without a comparison group (control). The sample in this study were 15 people with hypertension in the work area of the Sempaja Public Health Center. To find out the difference in blood pressure with hypertension before and after being given a daily treatment of decoction of Black Garlic. Results: The result of statistical test analysis showed that the variable systolic blood pressure of p-value is 0.001 < 0.05, and diasttolic blood pressure of p-value is 0.000 < 0.05. Conclusion: The result showed that there was a significant influence on blood pressure before and after giving black garlic.